2003
DOI: 10.1104/pp.103.022178
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Influx and Accumulation in Arabidopsis

Abstract: Arabidopsis is frequently used as a genetic model in plant salt tolerance studies, however, its physiological responses to salinity remain poorly characterized. This study presents a characterization of initial Na ϩ entry and the effects of Ca 2ϩ on plant growth and net Na ϩ accumulation in saline conditions. Unidirectional Na ϩ influx was measured carefully using very short influx times in roots of 12-d-old seedlings. Influx showed three components with distinct sensitivities to Ca 2ϩ , diethylpyrocarbonate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
273
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 244 publications
(303 citation statements)
references
References 65 publications
20
273
1
3
Order By: Relevance
“…Indeed, reported unidirectional Na + fluxes across the plasma membrane, as measured with CATE or with short-term tracer uptake experiments, appear at times to be too high to be energetically feasible (Britto and Kronzucker 2009). When coupled with even the small cytosolic exchange half-times for Na + found in the literature (Essah et al 2003), these values can, with CATE, result in cytosolic [Na + ] values an order of magnitude higher than those reported using electrodes see below). Perhaps because of uncertainties with these and other methods, ion-specific microelectrode measurements of cytosolic Na + accumulation have become the new standard (Munns and Tester 2008).…”
Section: Osmotic and Ionic Effects: What Is The Difference?mentioning
confidence: 74%
See 3 more Smart Citations
“…Indeed, reported unidirectional Na + fluxes across the plasma membrane, as measured with CATE or with short-term tracer uptake experiments, appear at times to be too high to be energetically feasible (Britto and Kronzucker 2009). When coupled with even the small cytosolic exchange half-times for Na + found in the literature (Essah et al 2003), these values can, with CATE, result in cytosolic [Na + ] values an order of magnitude higher than those reported using electrodes see below). Perhaps because of uncertainties with these and other methods, ion-specific microelectrode measurements of cytosolic Na + accumulation have become the new standard (Munns and Tester 2008).…”
Section: Osmotic and Ionic Effects: What Is The Difference?mentioning
confidence: 74%
“…Interestingly, these are levels at which little enzyme inhibition occurs (Greenway and Osmond 1972;Munns and Tester 2008), so mechanisms of Na + -specific toxicity may need to be sought elsewhere. Of additional importance is the conundrum that these low values, relative to CATE and other methods, suggest that either unidirectional Na + fluxes reported across the membrane using tracers (Britto and Kronzucker 2009), or exchange half-times for cytosolic Na + pools (Essah et al 2003), have been substantially overestimated. Another way to look at this problem is to predict cytosolic pool sizes on the basis of unidirectional influx across the plasma membrane and exchange halftimes for the cytosol (Cram 1969;MacRobbie 1971;Kronzucker 2001, 2003).…”
Section: Osmotic and Ionic Effects: What Is The Difference?mentioning
confidence: 99%
See 2 more Smart Citations
“…An unamended nutrient solution was used as the control. La(NO 3 ) 3 and CsCl have previously been identified as cation channel blockers by White (1997) and by Essah et al (2003), who also reported appropriate application concentrations. The Pb concentrations in our experiments were maintained at 20 lM.…”
Section: Effects Of Cation Channel Blockers On Pb Influxmentioning
confidence: 91%